2020
DOI: 10.1007/s00520-020-05354-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and distress in elderly vs. younger patients with high-grade glioma—results of a multicenter study

Abstract: Objective Half of all newly diagnosed patients with glioblastoma are > 65 years still with a poor prognosis. Preserving quality of life is of high importance. However, patient reported outcome (PRO) data in this patient group is rare. The aim was to compare health-related quality of life (HRQoL) and distress between elderly and younger patients with high-grade glioma (HGG). Methods We used baseline data of a prospective study where HGG patients were enrolled from 4 hospitals. Distress was measured using the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…There was no statistically significant difference in NANO score and ECOG performance status, and age was not a relevant factor for psychological distress. Similar findings were reported previously in glioma patients, where emotional functioning and DT scores were comparable between younger and elderly patients [28].…”
Section: Watch-and-wait Vs Operative Strategysupporting
confidence: 91%
“…There was no statistically significant difference in NANO score and ECOG performance status, and age was not a relevant factor for psychological distress. Similar findings were reported previously in glioma patients, where emotional functioning and DT scores were comparable between younger and elderly patients [28].…”
Section: Watch-and-wait Vs Operative Strategysupporting
confidence: 91%
“…Therefore we used KPS as an assessment tool of independent status. Several previous studies reported the close association between KPS and HRQoL or cognition ( 16 , 32 , 33 ) but KPS might not be sensitive enough to cognition impairment ( 20 ). This is also the most important limitation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In several recent studies, functional independence is defined by a KPS >70 (17,22). Assessing evolution over of the KPS is important because functional independence is a key factor for QoL and is emerging as an important endpoint in clinical trials (13)(14)(15)32). Although the HRQoL scale could obtain multi-dimensional details of function deficits, the complex assessment process and high training demand might limit the use of both clinicians and patients (3,33).…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed that age, Karnofsky performance scale score, education level, tumor grade, and psychological resilience were related to postoperative QOL. It has been reported that the main reason for the decline of QoL in elderly patients with glioma compared with young patients is that elderly patients have a more obvious decline in their physiological function ( 28 ). Educational level was also previously found to be associated with postoperative QoL in glioma patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%